Is Personality Profile a Relevant Determinant of Fatigue in Multiple Sclerosis? - Schreiber, Herbert; Lang, Michael; Kiltz, Kristina; Lang, Charlotte (Frontiers in Neurology, 2015)
The origin and pathophysiological background of MS-associated fatigue is poorly understood. There is no unifying concept of its nature and its determinants to date. This paper reviews possible influences of factors determining personality profile on mental fatigue in MS. Likewise, the role of psychological factors and their interaction with personality to promote fatigue is discussed. Current data suggests that fatigue, especially in early MS states, may be influenced by vulnerable personality traits and personality-associated features. Among them are depressive disease coping, avoidance behavior and inhibition, irritability, less extraversion, neuroticism, disturbed reward responsiveness and somatization behavior. However, among the validated personality factors no genuine influences that are independent of depression have been documented. From a psychological perspective, depressiveness, anxiety and perhaps somatization may be relevant mediators of fatigue. Interesting to note that in early MS a psychiatric diagnosis is significantly more likely than on a later stage of the disease and that fatigue and motivation might share neural circuits. It is hypothesized that psychological factors promote fatigue in MS by psychological distress and sustained neuro-endocrine and neurovegetative stress response. Despite there are limitations of data as discussed in the paper, personality research might help to disentangle specific promoting factors of fatigue in MS. Further research efforts are warranted since they might open ways to early psychological intervention of MS-associated fatigue. This is all the more important since medication is insufficient until now.